Age- and sex-based differences in exertional heat stroke incidence in a 7-mile road race - Belval, L. N.; Giersch, G. E. W.; Adams, W. M.; Hosokawa, Y.; Jardine, J. F.; Katch, R. K.; Stearns, R. L.; Casa, D. J. (Journal of Athletic Training, 2020)
Context: Sex, age, and wet-bulb globe temperature (WBGT) have been proposed risk factors for exertional heat stroke (EHS) despite conflicting laboratory and epidemiologic evidence. Objective: To examine differences in EHS incidence while accounting for sex, age, and environmental conditions. Design: Observational study. Setting: Falmouth Road Race, a warm-weather 7-mi (11.26-km) running road race. Patients or Other Participants: We reviewed records from patients treated for EHS at medical tents. Main Outcome Measure(s): The relative risk (RR) of EHS between sexes and across ages was assessed with males as the reference population. Multivariate linear regression analyses were calculated to determine the relative contribution of sex, age, and WBGT to the incidence of EHS. Results: Among 343 EHS cases, the female risk of EHS was lower overall (RR = 0.71; 95% confidence interval [CI] = 0.58, 0.89; P = .002) and for age groups 40 to 49 years (RR = 0.43; 95% CI = 0.24, 0.77; P = .005) and 50 to 59 years (RR = 0.31; 95% CI = 0.13, 0.72; P = .005). The incidence of EHS did not differ between sexes in relation to WBGT (P > .05). When sex, age, and WBGT were considered in combination, only age groups <14 years (ß = 2.41, P = .008), 15 to 18 years (ß = 3.83, P < .001), and 19 to 39 years (ß = 2.24, P = .014) significantly accounted for the variance in the incidence of EHS (R2 = .10, P = .006). Conclusions: In this unique investigation of EHS incidence in a road race, we found a 29% decreased EHS risk in females compared with males. However, when sex was considered with age and WBGT, only younger age accounted for an increased incidence of EHS. These results suggest that road race medical organizers should consider participant demographics when organizing the personnel and resources needed to treat patients with EHS. Specifically, organizers of events with greater numbers of young runners (aged 19 to 39 years) and males should prioritize ensuring that medical personnel are adequately prepared to handle patients with EHS.